Zoneamento Fito - Ecológico da Estação Ecológica de Aiuaba -uma contribuição à Educação Ambiental e à pesquisa científica - Medeiros, Jeanne Barros Leal de Pontes (2004)
The Aiuaba’s Ecological Station is located in Aiuaba town, Ceara State, and lies between 6036’ 01” to 6º44’ 35” south lattitude and 40o44’ 35” to 40º19’ 19” west longitude. In an 11.525ha area, it is covered by arboreal caatinga in almost its total extension and it is mainly represented by flat relief and litolic soils. The erosive forms are more frequent and the phyllite rocks are predominant. The Ecological Station represents an integral protection area of the caatinga ecosystem and because of its importance, the environmental data obteined during the project “Ecodynamic Researches in the Brazil Northeast’s Ecological Stations” were used to the ecological zoning of the area. The research methodology we used attempted to interpret the Station’s vegetation map,identifying the geological and geomorphological aspects, the kinds of soil and the altimetry within the area occupied by each sort of vegetation. The maps were initially transferred with a scanner to the Cartalinx software and after moved to Idrisi 3.22 in order to study the geoenvironmental units. We have defined seven management zones, which five of them onstitute real zones and two of them can be considered special zones. From these results, we purposed a management plan that contains basic programs (administrative, protective, of training and research and of environmental education), fundamentally important to make the Aiuaba’s Ecological Station dynamic as a natural wealthy space that deserves not only to be preserved, but also valued, used and understood by general community.